Serum Bicarbonate Changes Among Patients on Thrice Weekly Maintenance Hemodialysis (HD): A Single-Center Study: Serum Bicarbonate Changes Among Patients on Thrice-Weekly MHD - Javed, Hira; Anwar, Shahid; Yaqub, Muhammad Salman; Ahmad, Sajjad; Raza, Syed Ali; Rauf, Sundus (Pakistan Journal of Health Sciences, 2025)
Metabolic acidosis in hemodialysis significantly affects morbidity and mortality. Understanding bicarbonate fluctuations is key to optimizing supplementation and dialysis protocols. Objectives: To determine the inter-dialytic and intra-dialytic changes in serum bicarbonate level among patients undergoing maintenance hemodialysis. Methods: This quasi-experimental study was conducted at the Nephrology Department, Fatima Jinnah Medical University (FJMU)/Sir Ganga Ram Hospital, Lahore, after taking synopsis approval from the CPSP from August 2024 to January 2025. After taking consent, 60 patients on maintenance haemodialysis thrice weekly who met the selection criteria were enrolled. Inter-dialytic and intra-dialytic changes in serum bicarbonate levels were determined. Data were analyzed using SPSS version 26.0. Numerical values were presented as mean ± SD, and continuous variables were analysed using frequency and percentages. Inter-dialytic and intra-dialytic changes in bicarbonate levels were compared using a paired t-test; p≤0.05 was taken as significant. Results: Pre-hemodialysis mean bicarbonate level was 18.65 ± 1.11 mEq/L, increased to 22.18 ± 0.85 mEq/L post-hemodialysis, and by the next hemodialysis session, the mean pre-HD bicarbonate level reduced to 18.78 ± 1.02 mEq/L. Intra-dialytic change showed a mean increase of 3.53 ± 1.19 mEq/L, p-value<0.001 and inter-dialytic change demonstrated a decrease of 3.40 ± 1.18 mEq/L, p-value<0.001. Conclusions: It was concluded that hemodialysis temporarily raises bicarbonate levels, but they drop before the next session, highlighting the need for optimized supplementation or dialysis adjustments to maintain stability.